How should indocyanine green dye angiography be assessed to best predict mastectomy skin flap necrosis? A systematic review. Issue 6 (June 2020) - Driessen, Caroline; Arnardottir, Tinna Harper; Lorenzo, Andres Rodriguez; Mani, Maria Rydevik
Abstract: Introduction: The incidence of skin flap necrosis after mastectomies is as high as 11–24%. Laser-assisted indocyanine green (ICG) angiography seems to be a promising technique to assess skin flap perfusion. The aim of this systematic review is to assess the current methodology of ICG and its objective outcome measures ability to predict mastectomy skin flap necrosis. Methods: A PubMed search was conducted on the 31 December 2018 using ((("Fluorescein Angiography"[Mesh]) OR ("Indocyanine Green"[Mesh])) AND "Mastectomy"[Mesh]). This systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We included data about the study size, study design, skin flap necrosis, camera details and the objective outcome parameters. Results: Of 51 results, 22 abstracts were considered relevant of which nine were excluded secondarily. A reference check resulted in three extra inclusions. Sixteen papers were reviewed focusing on their methods and our primary endpoint which was the objective outcome measures of ICG. Objective outcome measures were reported in 8 of 16 studies. They mainly include absolute perfusion units and relative perfusion units (RPUs). All studies revealed a substantial decrease in skin necrosis when the ICG was used. The absolute number of units considered to be predictive for necrosis varies greatly; RPUs have been quite well established and are considered to be predictive for necrosis between 15.6% and 41.6%. However, consensus for methods, numbers and parameters is lacking. Conclusion: ICG evaluation of skin perfusion is a promising technique to aid in the surgeon's decision-making, and this seems to decrease skin flap necrosis after mastectomy.